Exploring Public Speaking Anxiety: Does Gender Really Matter? - Haya Aulia; Sari, Ratih Novita (LPPM Universitas PGRI Semarang, 2025)
This study aims to identify differences in public speaking anxiety levels between male and female students. A quantitative approach with a comparative design was used. The participants consisted of all 194 twelfth-grade students at SMAN 61 Jakarta, including 83 male and 111 female students. Data were collected through a questionnaire adapted from the Personal Report of Public Speaking Anxiety, which was translated and revalidated to suit the participant context. After a validity test, 27 items were included in the analysis. Anxiety scores were calculated using a three-step formula and categorized into low, moderate, and high levels. Data analysis was conducted using descriptive statistics and an independent samples t-test with SPSS version 29. The results showed no significant difference in public speaking anxiety between male and female students. However, descriptive findings indicated that female students generally showed slightly higher anxiety levels. This suggests that anxiety is influenced more by personal factors than gender. Educators are encouraged to provide equal speaking opportunities and build supportive classroom environments for all students.